2017
DOI: 10.1002/ente.201600731
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Hydrate Formation Promoted by a Natural Amino Acid l‐Methionine for Possible Application to CO2 Capture and Storage

Abstract: We demonstrate that l‐methionine, a natural amino acid, can be used to dramatically enhance CO2 uptake kinetics in the formation of CO2 hydrate without the use of energy‐intensive mixing technologies or environmentally harmful chemicals. To the best of our knowledge, l‐methionine is the most effective promoter to enhance CO2 hydrate formation (at a concentration of 0.2 wt %, the gravimetric capacity reached up to 356 mg g−1 in 1000 min, and t90 (the time to achieve 90 % of this capacity) was only 15 min). We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 48 publications
(27 reference statements)
8
74
0
Order By: Relevance
“…Roosta et al [28] have demonstrated that the inhibition effect of uncharged amino acid tends to increase with the increasing length of side chains; therefore, L-methionine is expected to be better CO 2 hydrate promoter compared to L-valine due to lower hydrophobicity of the side chain. Cai et al [45] have tested CO 2 hydrate kinetics in the presence of L-methionine and found CO 2 hydrate formation kinetics and hydrate storage capacity to be dramatically improved. The effect of different concentrations on the formation rate and storage capacity was studied, and it was found that 0.2 wt% of L-methionine gave the optimal performance.…”
Section: Review Of the Role Of Amino Acids During Co 2 Hydrate Formationmentioning
confidence: 99%
“…Roosta et al [28] have demonstrated that the inhibition effect of uncharged amino acid tends to increase with the increasing length of side chains; therefore, L-methionine is expected to be better CO 2 hydrate promoter compared to L-valine due to lower hydrophobicity of the side chain. Cai et al [45] have tested CO 2 hydrate kinetics in the presence of L-methionine and found CO 2 hydrate formation kinetics and hydrate storage capacity to be dramatically improved. The effect of different concentrations on the formation rate and storage capacity was studied, and it was found that 0.2 wt% of L-methionine gave the optimal performance.…”
Section: Review Of the Role Of Amino Acids During Co 2 Hydrate Formationmentioning
confidence: 99%
“…Further, Cai et al . reported 0.141 mol/molH 2 O (or 346 mg/g) CO 2 gas consumption in l-met (0.5 wt%) system 22 . The gas uptake values obtained in the present study are comparable to these results.…”
Section: Resultsmentioning
confidence: 99%
“…In practice, the hydrate dissociation is measured with slower temperature ramp, i.e., 0.5 to 1.0 K/h, to determine phase stability points. Faster temperature ramping, however, leads to measurable deviations from computed phase boundary curve 22 . The primary goal of this study is to probe gas hydrate formation ability in the presence AAs, and not on the dissociation behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations